A model for underwater shaking table tests on the basis of different similar criteria. (January 2022) - Yun, Gaojie; Liu, Chunguang
Highlights: Water changes the dynamic characteristics and dynamic responses of structure under earthquake action. An effective and feasible underwater shaking table test can be carried out for large-span structures with irregular cross-section within the elastic similar criteria. The test model with the appropriately added mass design can better reflect the dynamic response of the prototype structure. The larger peak acceleration has no effect on the errors between the distorted model, the lacking-artificial mass model and the prototype. The size effect has a significant influence on the error of the dynamic response between the prototype and model. Abstract: Shaking table testing is still considered a reliable approach when examining the seismic performance of structures, however, for long-span and large-scale hydraulic structures, limited by the constraints of test equipment and the influence of water, during underwater shaking table testing, if the earthquakes input, water levels and similitude law obtained on the basis of the test model and the resulting similar relationship do not fall within the operating range of the shaking table, the obtained results cannot truly reflect the dynamic response of the tested structure. To solve this problem, the improved dimensional analysis method and the finite element software ANSYS are used to study similar relationships and derive the design model of a certain bridge. Within the elastic similarity criteria, effective and feasible test models are proposed. The distortion model is designed by increasing the added mass can reduce the time scale, guarantee that the test runs smoothly, and better reflect the dynamic response of the prototype structure after such modification, however, for the long and thin model structure, the appropriate added mass adopted to ensure that within the bearing capacity of the structure and the shaking table, the elastic similarity meets the design requirements of the structure model of irregular and regular cross-sections and is suitable for the model design requirements of long-span and large-scale structures. Within the elasticity-gravity similar criteria, the distortion model designed by added mass can reflect the dynamic response of the prototype structure, which needs to be configured with certain added masses, and the bearing capacity of the model itself and the shaking table needs to be considered. The elasticity-gravity similitude law is suitable for examining regular cross-sections and short-span and small-scale test models, but the fluid-structure coupling and failure mechanism of structures can be examined. The distinctive peak acceleration will not affect the error of the dynamic response of the lacking-artificial added mass model, the distortion model and the prototype. The reinforcement ratio will not affect the error of the dynamic response of the distortion model and the prototype structure, but it will affect the error of the dynamic response of the lacking-artificial added mass model and the prototype structure. The added mass of the water triggered by the flexible movement of the structure under the action of earthquake changes the dynamic characteristics of the structure and the rigid movement of the structure triggers the water to exert an external force on the structure, which affects the dynamic characteristics and responses of the structure. This paper can provide a reference for the examine of other hydraulic structures and is beneficial to the examine of applied ocean engineering problems.